ENHANCING NUCLEAR ENERGY DEVELOPMENT: THE ROLE OF THE NEW ENERGY BILL IN LEGAL AND REGULATORY FRAMEWORKS - Putra, Raihan Maulana (Student Journal of International Law, 2025)
This paper emphasizes the significance of the new energy bill in the development and operation of nuclear energy, highlighting the importance of a well-structured legal framework. The research employs normative-juridical methods to analyze relevant legal principles and regulations. Findings indicate that numerous international nuclear laws and regulations, which have been ratified or adopted, must be integrated into national legislation to ensure compliance and effective governance. The study also reveals significant opposition rooted in concerns over nuclear management failures, past nuclear accidents, and a shortage of qualified human resources. The impact of the Nuclear Non-Proliferation Treaty (NPT) underscores that nuclear power can be utilized peacefully for development and benefit, provided proper safeguards are in place. The research suggests that several implementing laws and nuclear security regulations remain insufficiently regulated and require prompt development. It advocates for the immediate enactment of the new and renewable energy bill, which should explicitly include provisions for nuclear power, emphasizing safety, security, and sustainable development. Incorporating nuclear energy into this legislation is crucial for advancing national energy security and aligning with international standards. The paper recommends that the government prioritize the formulation and enactment of comprehensive legal instruments to regulate nuclear energy effectively, ensuring safety, security, and sustainable use while addressing public concerns and international obligations.